Діагностика фінансової стійкості підприємства на основі руху грошових потоків - Сітак, Ірина Леонідівна; Мурашко, Ірина Миколаївна (Класичний приватний університет, 2019)
Стаття присвячена дослідженню методичних основ оцінювання фінансової стійкості. Розкрито окремі проблеми оцінювання фінансового стану та управління фінансовою стійкістю підприємств. Досліджено теоретичні питання значення та видів грошових потоків підприємств. Обґрунтовано, що поділ грошових потоків за видами операцій суб’єктів господарювання на грошові потоки від операційних, інвестиційних та фінансових операцій повинен залежати від обсягу операцій, а також потреб у цій інформації користувачів. Визначено заходи щодо збільшення позитивного грошового потоку. Розглянуто підходи до прогнозування руху грошових коштів задля ефективного управління грошовими потоками суб’єкта господарювання. Запропоновані в роботі пропозиції щодо оцінювання грошових потоків дадуть змогу підвищити рівень корисності та достовірності аналітичної інформації для прийняття управлінських рішень на підприємстві.

The article is devoted to the study of methodological foundations of financial stability estimation. Some problems in assessing financial status and managing financial sustainability of enterprises are disclosed. The theoretical questions of the value and types of cash flows of enterprises are investigated. It is substantiated that the division of cash flows by type of operations of economic entities into cash flows from operating, investment and financial operations should depend on the volume of these operations, as well as on the needs of this information of users. On the basis of the financial statements and the cash flow statement, for the study of cash flows, steps can be used that should include a method for analyzing cash flows. The state of the flow of cash flows allows us to judge the quality of management of an enterprise. In general, cash flows from operating, investment and financial activities can move in different directions, which depend on the performance of the enterprise. Quantitative financial situation at the enterprise, taking into account possible three situations, that is, cash flows from operational, investment and financial activity is proposed to be determined using the formula for estimating the financial stability ratio, which characterizes a positive or negative change in this movement. This indicator indirectly reflects the factors of financial and non-financial nature of the enterprise. Information on cash flows is important because it allows you to predict the future amount of funds that the vendors of the company’s equity will have, as well as enable timely management decisions based on current reporting information. Management actions in achieving a high stability zone are aimed at the further conduct of permanent monitoring. Measures to increase the positive cash flow are determined. Approaches to forecasting of cash flow for the purpose of effective management of cash flows of the enterprise are considered. The proposed proposals for the evaluation of cash flows will increase the usefulness and reliability of analytical information for making management decisions at the enterprise.
Diagnostics of the financial stability of the enterprise on the basis of cash flows
Keywords: фінансова стійкість; грошові потоки; рух грошових коштів; операційна діяльність; фінансова діяльність; інвестиційна діяльність; управління підприємством; financial stability; cash flows; operations activities; financial activities; investment activities; management